2018
DOI: 10.4055/cios.2018.10.4.398
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Serum Albumin Levels Predict Treatment Cost in Total Hip and Knee Arthroplasty

Abstract: BackgroundHypoalbuminemia (serum albumin < 3.5 g/dL) is associated with increased morbidity and mortality in patients undergoing total hip arthroplasty (THA) and total knee arthroplasty (TKA). However, costs associated with hypoalbuminemia remain unknown. This study investigated the effect of serum albumin on direct treatment costs, length of stay (LOS), and readmissions for primary and revision THA and TKA patients.MethodsAll adult patients at a single institution undergoing primary or revision THA or TKA bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 15 publications
(35 reference statements)
4
29
1
Order By: Relevance
“…The preoperative albumin reflects the nutrition status of patients, which participates in the promotion of incision healing. A high pre-operative Alb could promote the incision healing, while a low serum Alb would lead to a variety of complications or even death [16,17]. Our study found that patients with preoperative Alb < 30 g/L had a longer LOS.…”
Section: Discussionmentioning
confidence: 52%
“…The preoperative albumin reflects the nutrition status of patients, which participates in the promotion of incision healing. A high pre-operative Alb could promote the incision healing, while a low serum Alb would lead to a variety of complications or even death [16,17]. Our study found that patients with preoperative Alb < 30 g/L had a longer LOS.…”
Section: Discussionmentioning
confidence: 52%
“…Additionally, there is evidence to suggest that preoperative factors, including anemia and hypoalbuminemia, are associated with increased costs following surgery. [ 8 , 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…But HAS use has been associated with higher risk of cardiac, pulmonary, and combined complications, acute renal failure, and unplanned intensive care unit admission [12]. Furthermore, hypoproteinemia was directly associated with increased total costs in revision and primary TJA [11]. Clinicians and policy providers should consider this question for optimizing the nutritional status of patients preoperatively and reducing the risk factors that may increase medical costs in the ear of bundled payments for TJA [20].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to malnutrition, low serum albumin level is associated with various postoperative complications following TJA, which include pulmonary infection, renal impaired, super cial and deep infections, myocardial infarction, unplanned intubation, and even mortality [10]. Low serum albumin level is also related to increased treatment costs, longer length of stay, and higher risk of readmission [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation